2017
DOI: 10.1021/acs.jpcb.7b06295
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Cypridina Bioluminescence with a Combined Experimental and Theoretical Chemiluminescent Approach

Abstract: The bioluminescent reaction of the "sea firefly" Cypridina hilgendorfii is a prototypical system for marine bioluminescence, as its substrate possesses an imidazopyrazinone core that is a common link among organisms of eight phyla. The elucidation of the mechanism behind Cypridina bioluminescence is essential for future applications in bioimaging, biomedicine, and bioanalysis. In this study we have investigated the key step of chemiexcitation with a combined experimental and theoretical approach. The obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
131
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(151 citation statements)
references
References 83 publications
18
131
2
Order By: Relevance
“…However, even CTIL have failed to explain some experimental and theoretical results. Theoretical calculations have shown that neutral imidazopyrazinone‐based dioxetanones present more efficient S 0 →S 1 chemiexcitation pathways than anionic dioxetanones . This results from the fact that neutral peroxides have access to a large and flat potential energy surface (PES) region of degeneracy between S 0 and S 1 states found within the biradical region.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…However, even CTIL have failed to explain some experimental and theoretical results. Theoretical calculations have shown that neutral imidazopyrazinone‐based dioxetanones present more efficient S 0 →S 1 chemiexcitation pathways than anionic dioxetanones . This results from the fact that neutral peroxides have access to a large and flat potential energy surface (PES) region of degeneracy between S 0 and S 1 states found within the biradical region.…”
Section: Introductionmentioning
confidence: 66%
“…These results once again put into question the validity of both CIEEL and CTIL mechanisms, as efficient chemiexcitation was ascribed to a neutral molecule instead of an ionized one. More relevant evidence regarding this topic was given by the analysis of the electron/charge density of neutral/anionic Cypridina dioxetanone, as a function of the thermolysis reaction . We found that despite both molecules undergoing different chemiexcitation pathways, both dioxetanone species decompose with significant ET/BET and CT/BCT between the imidazopyrazinone and dioxetanone moieties .…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations